2022
DOI: 10.3390/ijms232113496
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Induces Toxicity at Different Phenotypic, Physiological, Biochemical, and Ultrastructural Levels in Sweet Potato (Ipomoea batatas L.) Plants

Abstract: Crop productivity is enormously exposed to different environmental stresses, among which chromium (Cr) stress raises considerable concerns and causes a serious threat to plant growth. This study explored the toxic effect of Cr on sweet potato plants. Plants were hydroponically grown, and treatments of 0, 25, 50, 100, and 200 µM Cr were applied for seven days. This study exhibited that a low level of Cr treatment (25 µM) enhanced the growth, biomass, photosynthesis, osmolytes, antioxidants, and enzyme activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 75 publications
2
11
0
Order By: Relevance
“…Heavy metals treatment causes serious effect to the plants due to their respirational toxicity. Kumar et al (2022) reported the mechanism of chromium stress in the plants as low concentrations (25µM) showed enhanced growth rate, photosynthetic pigments and enzyme activities while increased concentrations showed remarkable stunned growth in Ipomoea batatas (L.) plants. Accumulation of Cr ions developed a stress in plant cell which resulted in the increased proline levels in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals treatment causes serious effect to the plants due to their respirational toxicity. Kumar et al (2022) reported the mechanism of chromium stress in the plants as low concentrations (25µM) showed enhanced growth rate, photosynthetic pigments and enzyme activities while increased concentrations showed remarkable stunned growth in Ipomoea batatas (L.) plants. Accumulation of Cr ions developed a stress in plant cell which resulted in the increased proline levels in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…V toxicity mediates stomatal abnormalities, such as a reduction in the stomatal length, width, pore length, and width of guard cells ( Figure 9 and Table 4 ). A study reported that the reduction in the stomata size is linked with more distorted stomata under an elevated level of heavy metals in the leaves [ 30 , 55 ]. Photosynthesis, transpiration, and gas exchange can be adversely affected by reductions in stomatal size and closure frequency.…”
Section: Discussionmentioning
confidence: 99%
“…To observe the stomatal morphology, we used a published protocol [ 30 ]. To remove any debris, leaves were acetylated in 80% ethanol for two to three min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Cr(VI) does not undergo biodegradation in soil, it is far more toxic than Cr(III) towards all living organisms, including plants [35]. Chromium induces changes in plants on the phenotypic, physiological, biochemical, and ultrastructural levels [36]. Admittedly, the response of plants to exposure to Cr is manifested by growth inhibition and decreased biomass, chlorosis, and deformation of the structure of chloroplasts through the peroxidation of fatty acids and lipids in their membranes induced by an increase in lipoxygenase [37,38].…”
Section: Introductionmentioning
confidence: 99%